Epidemiological Characteristics and Predisposing Factors for Surgical Site Infections Caused by Bacterial Pathogens Exhibiting Multidrug-Resistant Patterns - Abdikarim Hussein Mohamed; Hussein Ali Mohamud; Ebubekir Arslan (MDPI AG, 2021)
Background: Surgical site infection is the most common kind of nosocomial infection in developed and developing countries. Objectives: Our aim was to identify the prevalence of factors predisposing to multidrug resistance and the antimicrobial susceptibility profile of pathogens. Method: This retrospective study enrolled 10,878 patients who underwent operations in 2018-2020. Pathogens were identified using eosin methylene blue agar. Mueller-Hinton agar was used to assess antimicrobial sensitivity and resistance. In total, 382 patients with confirmed surgical site infection (SSI), whose culture showed growth, were included in the study. Results: The prevalence of SSI in the current study was 3.5%. Escherichia coli was the predominant pathogen (35.8%), followed by Staphylococcus aureus (21.8%). Antibiotic use, chronic renal failure, diabetes, and emergency operations were found to increase the likelihood of multidrug resistance (OR = 6.23, CI = 1.443-26.881, p = 0.014; OR = 5.67, CI = 1.837-19.64, p = 0.02; OR = 2.54, CI = 1.46-7.35, p = 0.03; OR = 1.885, CI = 1.067-3.332, p = 0.002, respectively). The pathogens showed different levels of antimicrobial resistance against ceftriaxone (72.7%), ciprofloxacin (46.6%), and gentamicin (34%). Antimicrobial resistance of about 1-3.4% was exhibited by linezolid, tigecycline, and teicoplanin. Conclusion: The study presented significantly increased multidrug-resistant (MDR) Enterobacteriaceae pathogens isolated from surgical sites. They involve significant morbidity and mortality rates and increased health-related costs.